Distinct Roles for KASH Proteins SINE1 and SINE2 in Guard Cell Actin Reorganization, Calcium Oscillations, and Vacuolar Remodeling - Biel, Alecia; Moser, Morgan; Groves, Norman R.; Meier, Iris (Frontiers in Plant Science, 2022)
The Linker of Nucleoskeleton and Cytoskeleton (LINC) complex is a protein complex spanning the inner and outer membranes of the nuclear envelope. Outer nuclear membrane KASH proteins interact in the nuclear envelope lumen with inner nuclear membrane SUN proteins. The paralogous Arabidopsis KASH proteins SINE1 and SINE2 function during stomatal dynamics induced by light-dark transitions and ABA. Previous studies have shown F-actin organization, cytoplasmic calcium (Ca2+) oscillations, and vacuolar morphology changes are involved in ABA-induced stomatal closure. Here, we show that SINE1 and SINE2 are required for actin pattern changes during ABA-induced stomatal closure, but are required for discreet, temporally distinguishable steps. Ca2+ partially rescues impairments in closing and actin patterns. ABA-induced cytoplasmic Ca2+ oscillations are diminished in sine2-1 but not sine1-1, and this defect can be rescued by both exogenous Ca2+ and F-actin depolymerization. We show first evidence for nuclear calcium oscillations during ABA-induced stomatal closure, which are disrupted in sine2-1. Vacuolar fragmentation is impaired in both mutants, and is partially rescued by F-actin depolymerization. Together, these data indicate distinct roles for SINE1 and SINE2 upstream of this network of players involved in ABA-based stomatal closure, suggesting a role for the nuclear surface in guard cell ABA signaling.